Characterization of resistance to crenate broomrape (Orobanche crenata) in a new small-seeded line of Tunisian faba beans - Abbes, Zouhaier; Kharrat, Mohamed; Simier, Philippe; Chaïbi, Wided (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ), 2007)
AbstractOrobanche crenata, crenate broomrape, causes major drawbacks in faba bean production in Mediterranean countries. The development of resistant varieties remains the most efficient way to solve this problem. This study was designed to assess the resistance of the breeding line XBJ90.03-16-1-1-1-1 to crenate broomrape, using cv. Bachaar as a susceptible control. Incidence and severity parameters were evaluated in infested fields to values reaching 95% and 4 (on a 1 to 9 scale), respectively, in 'Bachaar', and reaching only 5% and 1.5, in 'XBJ90.03-16-1-1-1-1'. This selected line displayed, at the most, an average of one emerged crenate broomrape individual per plant at crop maturity, whereas 'Bachaar' plants displayed five emerged broomrape individuals under the same conditions. In addition, the seed yield of 'XBJ90.03-16-1-1-1-1' plants was two-fold higher than that of 'Bachaar'. In pot experiments, number and total dry weight of broomrape individuals per plant were significantly higher for 'Bachaar' than for 'XBJ90.03-16-1-1-1-1'. In root chambers, percent germination of broomrape seeds was five-fold lower in the vicinity of 'XBJ90.03-16-1-1-1-1' roots (3%) than close to 'Bachaar' roots (15%). The direct consequence was a limited number of broomrape tubercles per 'XBJ90.03-16-1-1-1-1' plant. Furthermore, tubercle formation on 'XBJ90.03-16-1-1-1-1' roots was delayed by a week compared with the infection process on 'Bachaar' roots. Finally, some features of 'XBJ90.03-16-1-1-1-1' roots were characterized, such as the low amount of exudation of germination stimulant, which, combined with a deep root system, triggers resistance to the parasite.